Isolation of mitochondrial control region for white-nest swiftlets (Aerodramus fuciphagus) using primer walking techniques - Goh, W.L; Lim, C.K; Rahman, M.A (Universiti Putra Malaysia, 2013)
This paper reports on a novel DNA sequence located at the mitochondrial control region (D-loop) of the white-nest swiftlet (Aerodramus fuciphagus). This hypervariable control region sequence is potentially useful for studying genetic relationships among the white-nest swiftlet populations. The isolation of the control region involves a primer walking technique, which is simple, fast and cost-effective. In this study, the variability of the control region was assessed and discussed.